The jumbo carbon footprint of a shrimp carbon losses from mangrove deforestation - Kauffman, J.B.; Arifanti, V.B.; Trejo, H.H.; Carmen Jesús García, M. del; Norfolk, J.; Cifuentes, M.; Hadriyanto, D.; Murdiyarso, Daniel (Wiley, 2017)
Scientists have the difficult task of clearly conveying the ecological consequences of forest and wetland loss to the public. To address this challenge, we scaled the atmospheric carbon emissions arising from mangrove deforestation down to the level of an individual consumer. This type of quantification represents the “land‐use carbon footprint”, or the amount of greenhouse gases (GHGs) generated when natural ecosystems are converted to produce commodities. On the basis of measurements of ecosystem carbon stocks from 30 relatively undisturbed mangrove forests and 21 adjacent shrimp ponds or cattle pastures, we determined that mangrove conversion results in GHG emissions ranging between 1067 and 3003 megagrams of carbon dioxide equivalent (CO2e) per hectare. There is a land‐use carbon footprint of 1440 kg CO2e for every kilogram of beef and 1603 kg CO2e for every kilogram of shrimp produced on lands formerly occupied by mangroves. A typical steak and shrimp cocktail dinner would burden the atmosphere with 816 kg CO2e. This is approximately the same quantity of GHGs produced by driving a fuel‐efficient automobile from Los Angeles to New York City. Failure to include deforestation in life‐cycle assessments greatly underestimates the GHG emissions from food production.